TRANSFORMATIONAL ANALYSIS OF AUXILIARY ON THE MAIN ARTICLE OF THE JAKARTA POST PUBLISHED ON JANUARY-FEBRUARY 2008 - FIRMANSYAH, ERICK (2010)
This research is aimed to prove that auxiliary emerges in all sentences. It is, then, interpreted to the objectives; to identify the auxiliary from the data and to explain its transformational process. To reach those objectives, it is needed to implement the theory of Transformational Grammar. It is believed that this theory is the only relevant theory since it is the only theory which breaks down sentence into deep structure and surface structure.